2021
DOI: 10.3390/jcm10112486
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality vs. Tablet Video as an Experiential Education Platform for Pediatric Patients Undergoing Chest Radiography: A Randomized Clinical Trial

Abstract: Virtual reality (VR), which offers an immersive experience, has been implemented into the education of pediatric patients to reduce peri-procedural anxiety. This randomized clinical trial evaluated the effect of VR, compared with standard video, on reducing anxiety and distress in pediatric patients undergoing chest radiography. A total of 120 children aged 4 to 8 years with scheduled chest radiography appointments were randomized into either the tablet or the VR group. Children in the tablet group experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Previous studies have reported that VR education reduced periprocedural or perioperative anxiety in children, which is consistent with our results ( 13 16 ). Compared to 2-dimensional video education, 360°C 3-dimensional VR experience of the same content significantly reduced periprocedural anxiety in children undergoing chest radiography, which demonstrated the superior educational effect of VR ( 14 ). In the field of psychiatry, VR is utilized as an emerging method of exposure ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that VR education reduced periprocedural or perioperative anxiety in children, which is consistent with our results ( 13 16 ). Compared to 2-dimensional video education, 360°C 3-dimensional VR experience of the same content significantly reduced periprocedural anxiety in children undergoing chest radiography, which demonstrated the superior educational effect of VR ( 14 ). In the field of psychiatry, VR is utilized as an emerging method of exposure ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of all the studies included are reported in Table 2. Out of 10 incoming studies, 3 studies (30%) in Korea [2,24,25] and other studies in Brazil [19], Iran [20], Netherlands [21], Saudi Arabia [22], Republic of Korea [1], Spain [23] and China [3]. Studies in two categories of randomized trial (20%) [21,24] and randomized clinical trial (60%) [1-3, 19, 20, 22, 23, 25] Were classified.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…In 7 of the studies, children and parents were satisfied with the virtual reality intervention in reducing anxiety, and in all 7 cases, users were highly satisfied [1-3, 19, 23-25]. In 3 cases of studies found from virtual reality technology in reducing pediatric anxiety in dentistry [3,19,23], 4 cases before surgery [20,21,24,25], 2 cases related to anxiety before shelf radiography of breasts [1,2] and one case were used during preoperative anesthesia [22].…”
Section: The Effects Of Virtual Reality On Children's Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the hardware selected for interventions, 22.89% of the works used Mobile Devices such as Tablets and Smartphones, 48.30% used the Computer, around 20.34% Games consoles on the market for entertainment purposes such as Wii and Xbox and 8.47% of these studies used proprietary solutions with their own hardware development. Some interventions like Tennant et al [130], Ryu et al [157], Kakoschke et al [132], Amin, Ashfaq M., et al [104], Avcil et al [96], Hassett et al [69] used more than one hardware device to compare which approach among the groups of their clinical trials showed better results during their research.…”
Section: Technology Of Intervention Groups In Vrmentioning
confidence: 99%